Cancer survivors' experiences with financial toxicity: A systematic review and meta‐synthesis of qualitative studies. Issue 6 (5th May 2020) - Zhu, Zheng; Xing, Weijie; Zhang, Xiaoju; Hu, Yan; So, Winnie K. W.
Abstract: Objective: The aim of this study was to synthesize qualitative research evidence on cancer survivors' experiences with financial toxicity (FT). Methods: We carried out a systematic review of qualitative studies using a meta‐aggregation approach. Papers published prior to 31 August 2019, were collected from electronic databases, including PubMed/MEDLINE, MEDLINE (Ovid), EMBASE (Ovid), CINAHL (EBSCO), Web of Science, ProQuest Dissertations and Theses, and Cochrane Library (Wiley). Results: Six synthesized findings were derived from 14 studies covering cancer patients' awareness of FT, cancer‐related expenditures, and the risk factors, impacts, coping strategies, and unmet needs related to FT. Conclusions: Cancer survivors incur FT; however, their awareness of FT is limited. Cancer‐related FT has multiple impacts on survivors' lives. Although cancer survivors try to cope with FT through adjustments, they still have unmet needs for the management of FT. Nurses and social workers can play a critical role in helping survivors manage FT by increasing pre‐awareness of FT, strengthening emotional empowerment, and providing personalized informative support.